2013
DOI: 10.1098/rsbl.2013.0396
|View full text |Cite
|
Sign up to set email alerts
|

Androgen changes and flexible rutting behaviour in male giraffes

Abstract: The social organization of giraffes (Giraffa camelopardalis) imposes a high-cost reproductive strategy on bulls, which adopt a 'roving male' tactic. Our observations on wild giraffes confirm that bulls indeed have unsynchronized rut-like periods, not unlike another tropical megaherbivore, the elephant, but on a much shorter timescale. We found profound changes in male sexual and social activities at the scale of about two weeks. This so far undescribed rutting behaviour is closely correlated with changes in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…That sexual behavior is in some way related to an increase in fAM concentrations in adult bulls is supported by our data showing that in mixed sex groups, the older adult giraffe bulls (Ad1) had a further increase in fAM levels when sexually active. A similar finding was presented in a recent study on giraffes, where the oldest bulls also showed significantly higher fAM levels, when sexually active (Seeber et al, 2013). For a number of species, times of sexual activity are often correlated with elevated androgen levels, as for example shown in bison (Mooring et al, 2004) or African and Asian elephant (Ganswindt et al, 2005;Ghosal et al, 2013), with already minor changes in fAM levels being related to male sexual activity in elephants (Rasmussen et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…That sexual behavior is in some way related to an increase in fAM concentrations in adult bulls is supported by our data showing that in mixed sex groups, the older adult giraffe bulls (Ad1) had a further increase in fAM levels when sexually active. A similar finding was presented in a recent study on giraffes, where the oldest bulls also showed significantly higher fAM levels, when sexually active (Seeber et al, 2013). For a number of species, times of sexual activity are often correlated with elevated androgen levels, as for example shown in bison (Mooring et al, 2004) or African and Asian elephant (Ganswindt et al, 2005;Ghosal et al, 2013), with already minor changes in fAM levels being related to male sexual activity in elephants (Rasmussen et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…A male was considered to be sexually active if it emitted any of the following behaviors towards a female: courtship behavior, investigation of the females anogenital region, urine testing, mating and mate guarding (Seeber et al, 2013). Conversely, a bull was considered to be sexually inactive if he did not show any of these behaviors.…”
Section: Social and Behavioral Datamentioning
confidence: 99%
See 3 more Smart Citations